Memorandum on Ward Furniture / by Winifred L. Norrie (1931)
1931 1931 1930s 2 pages PRIVATE & CONFIDENTIAL MEMORANDUM ON WARD FURNITURE by WINIFRED L. NORRIE. Some hospitals are fortunate in having fully equipped wards but the majority have old fashioned furniture and are actually short of bed linen. This memorandum is confined to the personal furniture of a ward. BEDS The most important furniture in the ward is the beds. They should be of the right height (3'6") with taut springs and adjustable by turning a handle to four positions:- raised head, raised feet, sitting, and raised knees. Large rubber wheels are a necessity on a ward bed. Curtains should be fixed round every bed to run at least half down its length. They can be suspended from a rod which goes round four sides of it and when not in use can be tied to the two rear corners. The use of these curtains does much to reconcile patients to a public ward, especially women. At washing times they give privacy and keep away draughts. At night time they help to shut off the patient from the other activities of the ward, and so induce sleep. They also make for economy in screens, which they could match. A pulley fixed over the head of the patient is certainly worth the cost in comfort to the patient and labour saving for the nurse. The charts fixed on the curtain rail at the foot of the bed can be seen at once by the nurses but not the patient. BEDDING. The most convenient type of mattress is that used in the Army which is made up of three "biscuits''. The filling depends somewhat on the nature of the work of the ward, but hair and fibre is best for all ordinary use. Most hospitals suffer from a scanty supply of sheets. The ideal number should allow of two changes per bed per week, with a few extra for emergencies. Patients vary so much as to their need of blankets that no definite number can be laid down, except that an allowance of three per bed in the winter should allow for adjustments, but the blankets must always be supplemented with hot water bottles. The counterpanes used can add a cheerful note of colour. Rubber sheets should have calico fixed on both ends at least to allow for tucking under the mattress If a ward has adjustable beds comparatively few pillows are needed, and an allowance of two per bed would be sufficient. Without these beds four are often wanted for one bed. To the majority of patients an air or water cushion pillow is a necessity especially after an operation. One to every two beds is a good working number. In all hospitals water beds are available as the need arises. As a rule they are not allocated to particular wards. LOCKER. The details of the locker are matters of great importance to the patient because a good locker will do much to take away that feeling of helplessness which a patient feels. Most of the lockers in English hospitals seem to be designed for inconvenience. The first necessity is that the locker top should be higher than the bed and washable, with 292/842/1/7